Electronic structure, phonon spectra and electron–phonon interaction in ScB2 - Sichkar, S.M.; Antonov, V.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The electronic structure, Fermi surface, angle dependence of the cyclotron masses and extremal cross sections of the Fermi surface, phonon spectra, electron–phonon Eliashberg and transport spectral functions, temperature dependence of electrical resistivity of the ScB2 diboride were investigated from first principles using the fully relativistic and full potential linear muffin-tin orbital methods. The calculations of the dynamic matrix were carried out within the framework of the linear response theory. A good agreement with experimental data of electron–phonon spectral functions, electrical resistivity, cyclotron masses and extremal cross sections of the Fermi surface was achieved.